2008
DOI: 10.1007/s00134-008-1286-2
|View full text |Cite
|
Sign up to set email alerts
|

Austrian validation and customization of the SAPS 3 Admission Score

Abstract: The SAPS 3 Admission Score's general equation can be seen as a framework for addressing the problem of outcome prediction in the general population of adult ICU patients. For benchmarking purposes, region-specific or country-specific equations seem to be necessary in order to compare ICUs on a similar level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
55
4
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 16 publications
4
55
4
2
Order By: Relevance
“…25,26 Nevertheless, some studies have already suggested that SAPS 3 underestimates in-hospital mortality among general critical care patients, which may be due to the model itself. 27,28 On the other hand, APACHE IV and GRACE presented appropriate calibration and similar accuracy. Choosing between these scores depends on the aim.…”
Section: Discussionmentioning
confidence: 95%
“…25,26 Nevertheless, some studies have already suggested that SAPS 3 underestimates in-hospital mortality among general critical care patients, which may be due to the model itself. 27,28 On the other hand, APACHE IV and GRACE presented appropriate calibration and similar accuracy. Choosing between these scores depends on the aim.…”
Section: Discussionmentioning
confidence: 95%
“…In another study, Lopes Ferreira et al reported that an increase in SOFA score during the first 48 h in the ICU predicted a mortality rate of at least 50%, while a decreasing SOFA score is associated with a decrease in mortality rates from 50 to 27% [13]. Recently, the Simplified Acute Physiology Score (SAPS) 3 admission score's general equation can be seen as a framework for addressing the issue of outcome prediction in a general ICU adult population [32]. Jensen et al [11] showed that day-by-day procalcitonin changes can identify critically ill patients who are at high risk of ICU mortality.…”
Section: Discussionmentioning
confidence: 99%
“…SAPS 3 was developed in a heterogeneous population from various countries in Europe, North, South and Central Americas and Australasia, which may have contributed to improve its external validity. Some studies have validated these new versions in other populations [10][11][12][13][14][15][16][17][18][19], but to the best of our knowledge, they have never been compared with each other before. The objective of this study is to assess external validity of the 3 scores and to compare their performance in a Brazilian population.…”
Section: Introductionmentioning
confidence: 99%